Influence of chemical and physical conditions on the production of bacteriocin by Aeromonas hydrophila - Baghdad Science Journal (مجلة بغداد للعلوم)
Aeromonas hydrophila have been isolated as a cause of a cute gastroenteritis in 23 (5.6%) of 410 patients. Other bacterial enteropathogens have been isolated from 387 patients with diarrhea, were 19 different strains. A. hydrophila occurred more commonly in children with acute diarrhea, the results showed that 18(78.26%) isolates of A. hydrophila found in children under 10 years old ,distributed to 10(43.47%) in male and 8(34.78%) in female ,and in adults with diarrhea 5 (21.73%). In the other hand, we noticed frequency of isolation was higher in male 14(60.86%) when compared with 9(39.14%) in female. Six strains of A. hydrophila have been observed to have bacteriocin activity against 12 of 23 different A. hydrophila ,as well as Staphylococcus aureas, Pseudomonas aeruginosa, Escherichia coli, Enterobacter cloacea and Shigella dysenteria. The results showed Bacteriocin-like substances (BLS11) had isoinhibitory activity on 10 same A. hydrophila species and heteroinhibitory activity effects on all pathogenic bacterial strains used, while BLS5 showed isoinhibitory activity on 2 same A. hydrophila species and heteroinhibitory activity by effecting on gram negative only, and BLS3& BLS12 showed activity on E. coli isolates only, and none of BLS1& BLS10(isoinhibitory activity on 1 A.hydrophila respectively) had effect on all pathogenic bacteria. Among the standard laboratory media used Brain Heart Infusion broth (BHI) showed the maximum production and poor yields resulted from growth in Peptone Glyserol (PG) and Nutrient broth. We selected BLS11 to their wide range effect on same species and enteric pathogenic strains, to study the Influence of chemical and physical conditions on the production of BLS by A.hydrophila. The BLS11 preparations from A.hydrophila11 strains of A. hydrophila were tolerant to all three treatments of surfactant. In the other hand, effect of organic acid on BLS production BLS11 has been studied and showed no remarkable difference in zone of inhibition when used acetone as affecter element, while both of isopropanol and ethanol have narrow inhibition zone range when compared with control strain. These results indicated that most A. hydrophila might be harboring plasmid mediated bacteriocin like substance, and there are no relation between BLS production and number of plasmid bands present in bacteria.